Pengaruh Store Atmosphere, Experiental Marketing Dan Price Discount Terhadap Keputusan Pembelian Di Era Pandemi COVID-19 (Studi Kasus Pada Konsumen Starbuck Malang) - Muhammad Luqman Khais; Agus Widarko; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2021)
Abstract At this time, the competition faced by a company is getting tougher. Management within the company is required to be more careful in determining its business strategy, not only that, but company management is also expected to increase sales. Because the competition is getting tougher. be a challenge or a threat to business people. Like during this Pandemic, almost the entire world was affected by significant losses, with a decline in the world economy, and an increase in basic prices in various countries, including Indonesia, which is currently facing a critical period from the impact of Covid-19. The impact of the Covid-19 pandemic is quite high, for companies that do not call for government regulations, companies are threatened with being closed until legal procedures are revoked. This caused a lot of companies to go out of business because they could not comply with the applicable procedures. As well as the decline in purchases of a company's product. The purpose of this study is to examine the effect of Store Atmosphere, Experiential Marketing and Price Discount simultaneously on purchasing decisions at the Covid-19 pandemic era in Malang Coffee turbo, and the partial influence of Store Atmosphere, Experiential Marketing and Price Discount on purchasing decisions at the Covid pandemic era. -19 on the poor Coffee starbuck. This research is an explanatory study (expanatory record) with a quantitative approach. In this study, the sample used was 100 respondents who visited and bought Starbucks products. The results showed that there was a simultaneous influence between Store Atmosphere, Experiential Marketing and Price Discount variables on the purchasing decision of Starbuck Coffee Malang on consumers of Starbuck Coffee Malang. It is known that partially there is an influence between Store Atmosphere, Experiential Marketing and Price Discount variables which have a partial effect on purchasing decisions of Starbuck Coffee Malang on consumers of Starbuck Coffee Malang. Keywords: Store Atmosphere, Experiential Marketing, Price Discount and Purchase Decisions